ISSUANCE OF A SURROGATE CERTIFICATE DUE TO BEING LOST BY AN HEIR, CAUSED BY A NATURAL DISASTER. - Fatmala, Faiqa (Universitas Tadulako, 2019)
Land registration is essentially aimed at ensuring the right of the landowner. The publication of a certificate is a safeguard to the landowners of their rights to the land, in order to provide legal certainty to the holders of land rights, land certificates are a strong proof. Ownership of the land is hereditary, if a person dies who leaves the inheritance in the form of land rights, then the inheritance falls to the heirs. Proof of ownership by the heirs is a certificate of inheritance endorsed by the sub-district head, in the process of issuing the replacement certificate lost due to natural disaster done first checking physical data and juridical data.